Exploring the Immersive Parasocial: Is it You or the Thought of You? - Hai-Jew, Shalin (My University, 2010)
Immersive and persistent 3D virtual spaces have been adopted for e-learning in higher education. These spaces involve multi-sensory, real-time interactivity with other learners through high-fidelity, human-embodied avatars as well as automated ‘bots; these involve virtual contexts that situate various types of learning. Practitioners have discussed promoting immersive addictions to support long-term, deep-transfer, and complex systems-based learning. The social presences of human-embodied avatars, in individuals and groups, and their communications-heavy interactivity, have encouraged the development of parasocial relationships in several forms: self-love of people for their own avatars (which they may build up with a range of attractive features and digital powers), and other-love for others’ online personas. Understanding the parasocial spectrum will be important for those heading into immersive multiverses, especially with campuses starting to offer full-service virtual and distance support systems that encourage distance learning without the hybrid / blended or any aspect of face-to-face (F2F). This position paper explores ways to build immersive learning and to communicate to elicit the salutary parasocial effects while avoiding possible negative ones.
Keywords: Parasocial; 3D immersive; Persistent virtual space; Human-embodied avatar; Social presence; Virtual relationships; Multiverses; Haptics